Contextual teaching and learning approach in social science: Its role to encourage pupils' cognitive learning achievement - Ruto, Rikardus; Mema, Anselmus; Nduru, Maria Purnama; Ota, Maria Kristina (Journal of Research in Instructional, 2021)
The research objective is to strengthen student learning outcomes using inquiry-based learning. This type of research is called classroom action research. This study's subjects were 34 students of class X MIPA 4 SMA Negeri 1 Wonomulyo, consisting of 12 boys and 22 girls. The instrument used to measure students' learning outcomes in this study was a multiple-choice test of 50. The indicator that shows the success of the research implementation is that students can achieve a minimum completeness value of 80% at a minimum standard score of 65. Based on the results of the classroom action research that has been implemented In SMA Negeri 1 Wonomulyo, it can be concluded that the application of the Inquiry learning model can improve student learning outcomes in class X MIPA 4 SMA Negeri 1 Wonomulyo. The increase in learning outcomes indicates the research results from cycle I to cycle II; namely, the average value of student learning outcomes increased from 26.47% to 88.23%.